The Influence of Spiritual Leadership and Religious Leadership on Employee Performance: The Mediating Role of Organizational Justice in Solo Peduli Employees - Salwa, Inastuti Raffi'ah; Asep Maulana Rohimat (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study aims to examine the influence of spiritual leadership and religious leadership on employee performance, with organizational justice as a mediating variable among Solo Peduli employees. Design/methodology/approach: The population in this study consists of a portion of Solo Peduli employees. The data collection technique used is a questionnaire. Data analysis is conducted using a descriptive method with a quantitative approach and processed using SmartPLS.his study employs a quantitative approach with a descriptive method. Data is collected through questionnaires and analyzed using SmartPLS. Research Findings: 1) Spiritual leadership has a significant and positive effect on employee performance. 2) Religious leadership has no effect on employee performance. 3) Organizational justice has a significant and positive effect on employee performance. 4) Organizational justice does not significantly mediate the influence of religious leadership on employee performance. Theoretical Contribution/Originality: This study contributes to the understanding of how spiritual leadership and religious leadership influence employee performance, emphasizing the role of organizational justice as a mediating variable in enhancing employee performance at Solo Peduli. Keywords: Spiritual Leadership, Religious Leadership, Employee Performance, Organizational Justice.